Interconnection of Islamic and Conventional Marketing in Muhammadiyah Charity Businesses - Basri, Bifa Fanisa; Hadi, Lukman; Nurudin, Agus (Idarotuna, 2024)
This article aims to analyze the interconnection between Islamic and conventional marketing in the context of Muhammadiyah Charity Business (AUM) in the health sector with a focus on the Referral and Information Management (MAMARUDI) program in the Islamic Hospital Cempaka Putih Jakarta. This research aims to understand how these two marketing approaches can work together to improve service quality and hospital competitiveness without ignoring Sharia principles, which are the main foundation of Muhammadiyah's Charity Business. With a qualitative approach, this research collects data through interviews, observations, and document analysis related to implementing the MAMARUDI program. The research results show that Islamic marketing, which focuses on honesty, can be combined with conventional marketing, which utilizes digital technology to expand reach and increase service efficiency. This interconnection increases patient confidence in hospital services and strengthens the reputation of the Cempaka Putih Islamic Hospital. This interconnection model offers an approach that can be applied in other Islamic health institutions to create professional services on Islamic values.